Negative and Positive Outflow-Feedback in Nearby (U)LIRGs - Cazzoli, Sara (Frontiers in Astronomy and Space Sciences, 2017)
The starburst-AGN coexistence in local (U)LIRGs makes these galaxies excellent laboratories for the study of stellar and AGN outflows and feedback. Outflows regulate star formation and AGN activity, redistributing gas, dust and metals over large scales in the interstellar and intergalactic media (negative feedback) being also considered to be able to undergo vigorous star formation (positive feedback). In this contribution, I will summarize the results from a search for outflows in a sample of nearby 38 local (U)LIRG systems observed with VIMOS/VLT integral field unit. For two galaxies of the sample I will detail the outflow properties and discuss the observational evidence for negative and positive outflow-feedback. The assessment of both negative and positive feedback effects represent a novel approach toward a comprehensive understanding of the impact of outflow feedback in the galaxy evolution.